Edukasi pemanfaatan kacang hijau sebagai peningkatan produksi ASI pada ibu postpartum - Dewi Parwati; Norma Safitri; Musdalifah Musdalifah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Low exclusive breastfeeding is caused by problems experienced by mothers in breastfeeding, one of which is the factor of breast milk production. The impact if breast milk does not come out is that the breasts can become swollen, mastitis and even abscesses. Lack of knowledge of postpartum mothers can cause babies to experience dehydration, malnutrition, diarrhea and jaundice. Purpose: Provide education about the use of green beans to increase breast milk production. Method: Counseling activities were carried out on January 7, 2025 at 09.00 WITA to 12.30 WITA at the Binanga Health Center, Mamuju District in collaboration with the LPPM Siti Fatimah Mamuju Health and Business Institute. The activity was attended by cadres and residents in the Binanga Health Center work area. The implementation was carried out by providing material related to green bean nutrition as a supporter of increasing breast milk production. As a measurement of the level of knowledge using a questionnaire media which was carried out before (pre-test data) and after (post-test data) the counseling activity. Results: Participants were quite enthusiastic in participating in the activity and stated that they would consume green beans regularly to increase breast milk production. Questionnaire data showed that before the counseling, it was 55% and after the counseling it increased to 87%, this indicates that there was an increase in participants' understanding of the importance of nutritional intake in increasing breast milk production.Conclusion: Educational activities about nutrition in the community provide a positive contribution to the knowledge and understanding of the success of mothers in providing nutrition to their babies and the causes of irregular breast milk production. There is an increase in public knowledge about the importance of optimal nutritional intake and green beans are one of the good vegetable proteins for smooth breast milk production. Suggestion: It is expected that health workers will guide the community to utilize materials or plants that are around the environment such as TOGA (Family Medicinal Plants) in meeting nutritional intake needs which will be easier, more affordable, and more economical. Keywords: Breast milk production; Green beans; Nutrition; Postpartum mothersPendahuluan: Rendahnya pemberian ASI Eksklusif disebabkan oleh masalah yang dialami oleh ibu dalam menyusui salah satunya adalah faktor pengeluaran produksi ASI. Dampak jika asi tidak keluar adalah payudara bisa bengkak, mastitis bahkan abses. Kurangnya pengetahuan ibu nifas dapat mengakibatkan bayi mengalami dehidrasi, kurang gizi, diare dan ikterus. Tujuan: Memberikan edukasi tentang pemanfaatan kacang hijau terhadap peningkatan produksi ASI. Metode: Kegiatan penyuluhan dilakukan pada tanggal 07 Januari 2025 pukul 09.00 Wita sampai 12.30 Wita di Puskesmas Binanga Kecamatan Mamuju bekerja sama dengan LPPM Institut Kesehatan dan Bisnis Siti Fatimah Mamuju. Kegiatan dihadiri oleh kader dan warga di wilayah kerja Puskesmas Binanga. Pelaksanaan dilakukan dengan memberikan pemaparan materi terkait nutrisi kacang hijau sebagai pendukung meningkatnya produksi ASI. Sebagai pengukuran tingkat pengetahuan menggunakan media kuesioner yang dilakukan sebelum (data pre-test) dan sesudah (data post-test) kegiatan penyuluhan.Hasil: Peserta cukup antusias dalam mengikuti kegiatan dan menyatakan akan mengonsumsi kacang hjiau secara rutin guna meningkatkan produksi ASI. Data kuesioner menunjukkan bahwa sebelum penyuluhan sebanyak 55% dan setelah penyuluhan meningkat menjadi 87%, hal ini menunjukkan terdapat peningkatan pemahaman peserta terhadap pentingnya asupan nutrisi dalam meningkatkan produksi ASI.Simpulan: Kegiatan edukasi tentang nutrisi pada masyarakat memberikan kontribusi positif terhadap pengetahuan dan pemahaman keberhasilan ibu dalam memberikan nutrisi kepada bayinya dan penyebab produksi ASI yang tidak lancar. Terdapat peningkatan pengetahuan pada masyarakat terhadap pentingnya asupan nutrisi dan gizi yang optimal dan kacang hijau adalah salah satu protein nabati yang baik untuk kelancaran produksi ASI.Saran: Diharapkan kepada tenaga kesehatan agar membimbing masyarakat untuk memanfaatkan bahan atau tanaman yang ada disekitaran lingkungan seperti TOGA (tanaman Obat Keluarga) dalam memenuhi kebutuhan asupan nutrisi/gizi dimana akan menjadi lebih mudah, terjangkau, dan ekonomis.